Laser Spectroscopy 2 Experimental Techniques - Demtröder, Wolfgang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
Keeping abreast of the latest techniques and applications, this new edition of the standard reference and graduate text on laser spectroscopy has been completely revised and expanded. While the general concept is unchanged, the new edition features a broad array of new material, e.g., ultrafast lasers (atto- and femto-second lasers), coherent matter waves, Doppler-free Fourier spectroscopy, interference spectroscopy, quantum optics and gravitational waves and still more applications in chemical analysis, medical diagnostics, and engineering.
Doppler-Limited Absorption and Fluorescence Spectroscopy with Lasers -- Nonlinear Spectroscopy -- Laser Raman Spectroscopy -- Laser Spectroscopy in Molecular Beams -- Optical Pumping and Double-Resonance Techniques -- Time-Resolved Laser Spectroscopy -- Coherent Spectroscopy -- Laser Spectroscopy of Collision Processes -- New Developments in Laser Spectroscopy -- Applications of Laser Spectroscopy -- Solutions.
Keywords: Spectroscopy; Microscopy; Optics; Electrodynamics; Microwaves; Optical engineering; Materials science; Spectroscopy and Microscopy; Classical Electrodynamics; Spectroscopy/Spectrometry.; Microwaves, RF and Optical Engineering; Characterization and Evaluation of Materials